Credibility of Serbian banking sector from the aspect of foreign direct investments - Mirković, Vladimir; Vujičić, Marija; Lukić, Jelena (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Foreign direct investments (FDIs) have extraordinary importance for the development of the country, contributing to the higher level of its competitiveness. Some transition economies were focused on FDIs attraction, selecting banking sector as one to the most propulsive targets. Using empirical evidence on FDIs in Serbian banking sector during XXI century through granular analysis by differentiation between greenfield and brownfield investments, this paper pinpoints on major movements and perspectives of development. Also, beside the FDIs aspect, which is the central point of the paper, this paper summarize the major regulatory changes in accordance with Basel III standards aimed to increase the credibility of Serbian banking sector.
Keywords: foreign direct investments; Serbian banking sector; Basel III standards